Leaders of the Libyan Jihad Movement Mujahid al - FadilBuamar Al – Awali Commander of the role of the tribes of Al-Abedat And Al-Hasain the region of Derna (1880 - 1930) (Journal of Human Sciences, 2018)
This research deals with the biography of the Mujahid Al-FadilBuammar al-Aujali Abu Hawa 1880-1931, his role in the Libyan Jihad movement, his positions in the fight against the Italian invaders and his sacrifices in order to uphold the word of truth .Al-Fadhil  was one of the mujahedeenheroes and a companion of Sheikh of martyrs Omar al-Mukhtar. He did not hesitate to defend his homeland since the beginning of the Italian invasion. He traveled from Oujla oasis to Jabal al-Akhdar to be with the mujahideen there to support his brother Mujahedeen and to offer his life for his homeland. This land with their bodies and Rurayt is the tree of freedom for this Yes,Al-FadilBuammar sacrificed his life in the Battle of Al-AtaroanValley in 1930 to live the next generations in freedom and prosperity, and he recorded his name in the record of heroes and honorable. Sine there is no enoughresearch about this characterdespite the great role that he haddone, it is my duty to write about him.And we hope that this research is adding a new knowledge to our Arabic library.